Catalytic-high temperature synergistic preparation method of lignin-based electromagnetic shielding carbon material
Through the Mn catalytic-high temperature synergistic graphitization method, the problem of poor graphitization effect of lignin is solved, efficient graphitization conversion and electromagnetic shielding performance are achieved, and the preparation process is environmentally friendly, avoiding the pickling step.
Patent Information
- Application Number
- CN202411722696.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, lignin has poor graphitization effect and requires transition metal catalysis. After the reaction, the metal needs to be removed by acid washing, which has environmental protection problems.
The Mn catalytic-high temperature synergistic graphitization method is used to achieve preliminary graphitization of lignin by catalysis of Mn at a relatively low temperature, and then the temperature is raised for catalytic-high temperature synergistic graphitization. Finally, the transition metal is removed by high temperature vaporization, avoiding the pickling step.
The efficient graphitization of lignin is achieved, the degree of graphitization of the product is greater than 50%, and the electromagnetic shielding effect is up to 21dB in the 1-8.5GHz band, reaching the level of medium shielding materials, and the preparation process is more environmentally friendly.
Smart Images

Figure CN119706820A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbonaceous material preparation and application, and mainly relates to a catalytic-high temperature synergistic preparation method of a lignin-based electromagnetic shielding carbon material. Technical Field
[0003] With the rapid development of the electronics industry, various electronic devices, such as computers and wireless communication devices, are becoming more and more popular. These electronic devices continuously radiate electromagnetic waves of various frequencies, thus causing electromagnetic pollution after air pollution and water pollution. It not only interferes with various electronic devices and electronic communications, but also has serious harm to human health. Therefore, the shielding of electromagnetic radiation and the development of shielding materials are particularly important. Electromagnetic shielding refers to the energy attenuation caused by electromagnetic waves being absorbed or reflected by shielding materials, thereby achieving the purpose of preventing electromagnetic waves from radiating to a specific direction.
[0004] The electromagnetic shielding effectiveness of a material is positively correlated with its conductivity. Therefore, the current electromagnetic shielding materials mainly include materials with conductive properties such as metals, conductive polymers, graphite, and graphene. At the same time, the more developed the pore structure of the material, the easier it is for electromagnetic waves to be lost due to multiple reflections inside it, which is conducive to improving its electromagnetic shielding effectiveness. Lignin has the significant advantages of a wide range of sources, a high yield of carbonized products, and a strong controllable carbon microcrystalline structure, and the current high-value utilization of lignin is still insufficient. Among wood fiber raw materials, although lignin is relatively easy to graphitize, it still requires an extremely high temperature of nearly 3000°C. Although transition metal-catalyzed graphitization can effectively reduce the temperature, previous studies have shown that this method is not ideal for lignin. Therefore, the present invention addresses this problem, firstly, at a relatively low temperature, the initial graphitization of lignin is achieved by catalysis of Mn, the temperature is continued to be increased to achieve catalytic-high temperature synergistic graphitization, and finally the temperature is further increased to gasify and remove the metal. Summary of the invention
[0005] In order to solve the shortcomings of the prior art in that the graphitization effect of lignin is poor, transition metal catalysis is required, the metal needs to be removed by acid washing after the reaction, and it is not environmentally friendly, the present invention provides a catalytic-high temperature synergistic preparation method of lignin-based electromagnetic shielding carbon material, which removes the transition metal after the reaction by high temperature gasification.
[0006] A lignin-based electromagnetic shielding carbon material is obtained by pyrolyzing and carbonizing lignin and then impregnating it with a mixture containing Mn 2+ The graphitization reaction is carried out in an aqueous solution in a non-reactive atmosphere, so that Mn is removed by high-temperature gasification, and the final product is obtained after cooling; the degree of graphitization is greater than 50%, and the shielding effectiveness in the 1-8.5 GHz band is up to 21dB.
[0007] The catalytic-high temperature synergistic preparation method of the lignin-based electromagnetic shielding carbon material comprises the following steps:
[0008] The first step is the pyrolysis and carbonization of lignin and the loading of metal catalysts: the lignin is fully carbonized at 400-600°C, and then the product is impregnated with a Mn-containing 2+ The obtained Mn-loaded carbon is then dried for later use;
[0009] In the second step, the carbon loaded with Mn is graphitized in a high-purity non-reactive gas atmosphere, and Mn is removed by high-temperature gasification, and the final product is obtained after cooling.
[0010] The Mn loading amount is 2-5 mmol / g C.
[0011] The graphitization reaction is divided into two stages, the temperature of the first stage is 1400-1800℃, and the temperature of the second stage is 2100-2400℃.
[0012] The first stage of graphitization reaction takes 2 to 5 hours, and the second stage takes 1 to 3 hours.
[0013] Beneficial effects:
[0014] 1. The Mn-high temperature synergistic catalytic method can effectively graphitize lignin at a relatively low temperature. The resulting product can achieve complete graphitization conversion, and its crystallinity is close to that of natural graphite. At the same time, its electromagnetic shielding effectiveness in the 1-8.5 GHz band can be close to 40 dB, reaching the level of medium shielding materials.
[0015] 2. The graphitization reaction is divided into two stages. The temperature of the first stage is relatively low, which is mainly the catalytic graphitization of Mn. The temperature of the second stage is higher, which is a catalytic-high temperature synergistic graphitization reaction. Finally, the temperature exceeds the boiling point of Mn, and Mn will escape in the form of vapor, avoiding the step of concentrated acid washing, making the preparation process more environmentally friendly, and also avoiding the risk of secondary pollution caused by using a large amount of concentrated acid to wash metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is the XRD spectrum of the lignin-based electromagnetic shielding carbon material treated at 1400℃~2200℃; sample treatment conditions: lignin pyrolysis at 600℃ - catalytic treatment at 1800℃ for 5h - treatment at 2400℃ for 3h.
[0017] Figure 2 This is a TEM photo of lignin-based electromagnetic shielding carbon material treated at 1400℃~2200℃; sample treatment conditions: lignin pyrolysis at 600℃ - catalytic treatment at 1800℃ for 5h - treatment at 2400℃ for 3h.
[0018] Figure 3 The shielding effectiveness curve of lignin-based electromagnetic shielding carbon materials treated at 1400℃ to 2200℃ against electromagnetic waves in the 1-8.5GHz band. Sample treatment conditions: lignin pyrolysis at 600℃, catalytic treatment at 1800℃ for 5h, and treatment at 2400℃ for 3h. The control sample was not impregnated with Mn2+, and the heating conditions in the graphitization reaction stage were the same. DETAILED DESCRIPTION
[0019] A catalytic-high temperature synergistic preparation method of a lignin-based electromagnetic shielding carbon material, the specific steps are as follows:
[0020] (1) The raw materials cellulose and lignin were fully dried at 140°C and placed in a sealed crucible for carbonization at 400-600°C for 1 hour. The carbonized product was immersed in a certain amount of Mn 2+ The mixture was placed in an aqueous solution of 2% NH overnight and then dried at 140°C for later use.
[0021] (2) The Mn-loaded pyrolytic carbon is placed in a graphite crucible and reacted in a graphitization furnace under a high-purity argon atmosphere for a certain period of time, and the final product is obtained after cooling.
[0022] Mn loading is 2-5 mmol / g C;
[0023] The temperature of the first stage of graphitization reaction is 1400-1800°C, and the temperature of the second stage is 2100-2400°C;
[0024] The first stage of graphitization reaction takes 2 to 5 hours, and the second stage takes 1 to 3 hours.
[0025] The prepared carbon was mixed with paraffin in a mass ratio of 2:3 by the coaxial method, and its electromagnetic shielding effectiveness in the 1-8.5 GHz band was tested by E-5071C vector network analysis.
[0026] In view of the problem that the catalytic graphitization effect of lignin is poor and that complete graphitization requires extremely high temperatures, the present invention adopts a Mn catalytic-high temperature synergistic graphitization method to successfully produce a product with a high degree of graphitization and a regular graphitized lamellar structure. The temperature required for this method is significantly lower than the conventional graphitization temperature, and Mn can be removed by gasification at above 2100°C, avoiding cumbersome pickling operations. In addition, the shielding effectiveness of the obtained product in the 1-8.5GHz band can be close to 40dB, reaching the level of medium shielding materials, and has good application prospects.
[0027] Embodiment 1:
[0028] Place lignin in a sealed crucible and carbonize at 400℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+The Mn loading was 3mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1400℃ in a graphitization furnace at a rate of 5℃ / min for 2h, and then the reaction temperature was raised to 2100℃ at the same heating rate and maintained for 1h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 51.7%, and its shielding effectiveness in the 1-8.5GHz band was up to 21dB.
[0029] Embodiment 2:
[0030] Place lignin in a sealed crucible and carbonize at 400℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+ The Mn loading was 3mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1400℃ in a graphitization furnace at a rate of 5℃ / min for 3h, and then the reaction temperature was raised to 2100℃ at the same heating rate and maintained for 1h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 54.1%, and its shielding effectiveness in the 1-8.5GHz band was up to 24dB.
[0031] Embodiment 3:
[0032] Place lignin in a sealed crucible and carbonize it at 500℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+ The Mn loading was 3mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1600℃ in a graphitization furnace at a rate of 5℃ / min for 3h, and then the reaction temperature was raised to 2200℃ at the same heating rate and maintained for 1h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 67.3%, and its shielding effectiveness in the 1-8.5GHz band was up to 29dB.
[0033] Embodiment 4:
[0034] Place lignin in a sealed crucible and carbonize it at 500℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+The Mn loading was 4mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1600℃ in a graphitization furnace at a rate of 5℃ / min for 3h, and then the reaction temperature was raised to 2200℃ at the same heating rate and maintained for 1h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 70.2%, and its shielding effectiveness in the 1-8.5GHz band was up to 31dB.
[0035] Embodiment 5:
[0036] Place lignin in a sealed crucible and carbonize at 500℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+ The Mn loading was 5mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1600℃ in a graphitization furnace at a rate of 5℃ / min for 5h, and then the reaction temperature was raised to 2400℃ at the same heating rate and maintained for 2h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 75.7%, and its shielding effectiveness in the 1-8.5GHz band was up to 35dB.
[0037] Embodiment 6:
[0038] Place lignin in a sealed crucible and carbonize at 500℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+ The Mn loading was 3mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1800℃ in a graphitization furnace at a rate of 5℃ / min for 3h, and then the reaction temperature was raised to 2200℃ at the same heating rate and maintained for 1h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 71.0%, and its shielding effectiveness in the 1-8.5GHz band was up to 33dB.
[0039] Embodiment 7:
[0040] Place lignin in a sealed crucible and carbonize at 500℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+The Mn loading was 4mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1600℃ in a graphitization furnace at a rate of 5℃ / min for 5h, and then the reaction temperature was raised to 2200℃ at the same heating rate and maintained for 3h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 76.8%, and its shielding effectiveness in the 1-8.5GHz band was up to 36dB.
[0041] Embodiment 8:
[0042] Place lignin in a sealed crucible and carbonize at 600℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+ The Mn loading was 4mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1600℃ in a graphitization furnace at a rate of 5℃ / min for 5h, and then the reaction temperature was raised to 2400℃ at the same heating rate and maintained for 3h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 79.1%, and its shielding effectiveness in the 1-8.5GHz band was up to 38dB.
[0043] Embodiment 9:
[0044] Place lignin in a sealed crucible and carbonize it at 500℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+ The pyrolytic carbon loaded with Mn was placed in a graphitization crucible and heated to 1800°C at a rate of 5°C / min in a graphitization furnace for 5 hours. The reaction temperature was then raised to 2200°C at the same rate and maintained for 1 hour. The reaction was carried out in a high-purity argon atmosphere and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 80.1% and a shielding effectiveness of up to 37dB in the 1-8.5GHz band.
[0045] Embodiment 10:
[0046] Place lignin in a sealed crucible and carbonize it at 500℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+The Mn loading was 4mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1800℃ at a rate of 5℃ / min in a graphitization furnace for 5h, and then the reaction temperature was raised to 2200℃ at the same heating rate and maintained for 3h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 83.4%, and its shielding effectiveness in the 1-8.5GHz band was up to 38dB.
[0047] Embodiment 11:
[0048] Place lignin in a sealed crucible and carbonize at 600℃ for 1h. Weigh 2g of pyrolytic carbon and soak it in a solution containing a certain amount of Mn 2+ The Mn loading was 5mmol / gC overnight in an aqueous solution, and then dried at 140℃ for later use. The Mn-loaded pyrolytic carbon was placed in a graphitization crucible, and first heated to 1800℃ in a graphitization furnace at a rate of 5℃ / min for 5h, and then the reaction temperature was raised to 2400℃ at the same heating rate and maintained for 3h. The whole reaction was carried out in a high-purity argon atmosphere, and the final product was obtained after cooling. The product was calculated to have a graphitization degree of 83.4%, and its shielding effectiveness in the 1-8.5GHz band was the highest.
Claims
1. A lignin-based electromagnetic shielding carbon material, characterized in that: After pyrolysis and carbonization of lignin, it is impregnated with 2 + The graphitization reaction is carried out in an aqueous solution in a non-reactive atmosphere, so that Mn is removed by high-temperature gasification, and the final product is obtained after cooling; the degree of graphitization is greater than 50%, and the shielding effectiveness in the 1-8.5 GHz band is up to 21dB.
2. A catalytic-high temperature synergistic preparation method of a lignin-based electromagnetic shielding carbon material according to claim 1, characterized in that: The following steps are involved: The first step is the pyrolysis and carbonization of lignin and the loading of metal catalysts: the lignin is fully carbonized at 400-600°C, and then the product is impregnated with a Mn-containing 2+ The obtained Mn-loaded carbon is then dried for later use; In the second step, the carbon loaded with Mn is graphitized in a high-purity non-reactive gas atmosphere, and Mn is removed by high-temperature gasification, and the final product is obtained after cooling.
3. The catalytic-high temperature synergistic preparation method based on a lignin-based electromagnetic shielding carbon material according to claim 2, characterized in that: The Mn loading amount is 2-5 mmol / g C.
4. The catalytic-high temperature synergistic preparation method based on a lignin-based electromagnetic shielding carbon material according to claim 2, characterized in that: The graphitization reaction is divided into two stages, the temperature of the first stage is 1400-1800℃, and the temperature of the second stage is 2100-2400℃.
5. The catalytic-high temperature synergistic preparation method based on a lignin-based electromagnetic shielding carbon material according to claim 2, characterized in that: The first stage of graphitization reaction takes 2 to 5 hours, and the second stage takes 1 to 3 hours.
Citation Information
Cited By
A lignin-based electromagnetic shielding carbon material and a preparation method and application thereof
CN122685041A